Extracorporeal life support for severe cardiogenic shock induced by diltiazem intoxication - Srdanovic, Ilija; Kovacevic, Mila; Stefanovic, Maja; Petrovic, Milovan; Cankovic, Milenko; Velicki, Lazar (Vojnosanitetski pregled, 2021)
Abstract Introduction. Management of cardiogenic shock caused by severe drug intoxication is always challenging. In case of multidrug intoxication, a result, despite aggressive medical therapy, is often unpredictable. Utilization of extracorporeal life support devices in these cases has been suggested and reported results are promising. Case report. We presented a case of profound cardiogenic and distributive shock caused by suicidal intoxication with diltiazem and anionic surfactant ingestion in a 36-year-old woman. The patient ingested more than 90 tablets of diltiazem of 90 mg (ingested dose of 8.1 g), and 4 pieces of household toilet refresh agent containing anionic surfactant. During the admission, systemic blood pressure was 65/40 mmHg, heart rate 45 beats per minute, with signs of metabolic acidosis. The patient underwent several repeated gastric lavages. Emergent fluid resuscitation, calcium gluconate, insulin and vasopressive agents (dopamine and noradrenaline) infusions were administered with negligible effect. Due to progressive and refractory cardiogenic shock with signs of multiorgan failure, a decision was made to put the patient on venoarterial extracorporeal membrane oxygenator. Immediately after starting the extracorporeal membrane oxygenation, diuresis was established. During the next 36 h, an adequate end-organ perfusion was achieved with complete reversal of multi-organ failure. After the successful restoration of all major organ functions, the patient was successfully decannulated and discharged from the hospital after 10 days in a good condition. Conclusion. In severe cases of refractory cardiogenic and distributive shock due to diltiazem and other poison intoxication, venoarterial extracorporeal membrane oxygenation could allow additional circulatory support providing the bonus time for endogenous clearance of toxins. Venoarterial extracorporeal membrane oxygenation could be used in conjunction with the optimal medical therapy aiming to the restoration of end-organ perfusion and allowing for intrinsic drug and toxin metabolism and natural elimination.
Keywords: calcium channel blockers; extracorporeal membrane oxygenation; poisoning; pulmonary edema; shock, cardiogenic; treatment outcome